Experiment on the effect of an interaction of heat and hypoosmotic stress on the growth and photosynthetic performance of tropical seagrass species Thalassia testudinum: photosynthetic performance - Csenteri, Katharina; Reusch, Thorsten B H; Willim, Jana; Provera, Isabella (PANGAEA, 2024)
This study examined the response of tropical seagrass species Thalassia testudinum to a combination of heat and hypoosmotic stress. These two stressors are of major importance, as studies predict a rise in sea surface temperatures, as well as in increase in precipitation in the Caribbean region. Field-studies revealed the plant to exhibit a slow stress response to e.g. elevated temperatures and changes in salinity, however, they also showed the severity in changes in these factors. While in-situ observations allow for a good setting of treatment levels, there is a scarcity of in-culture experiments exposing T. testudinum to heat and osmotic stress, especially in combination. These experiments are essential to precisely delineate the effects and establish causality, thereby eliminating potential confounding factors. This in-culture experiment was performed in the culturing facilities of the GEOMAR building (54°19'48N 10°08'54E) using a culture of four T. testudinum clones. Plants were originally collected in 2017 from waters in front of the Smithsonian Tropical Research Institute in Bocas del Toro, Panama (9°21'04N 82°15'26W). Subsequently, they were cultivated in the GEOMAR culturing facilities under water temperatures of 28°C and salinities levels between 31-34. For the experiment, plants were replanted in February 2023 to fit a fully factorial experiment comprising all four clones crossed over four treatments: control (T=28°C; S=32.5), heat stress (T=34°C; S=32.5), hypoosmotic stress (T=28°C; S=27) and combined heat and hypoosmotic stress (T=34°C; S=27). Each treatment held three replicates (100 L aquaria), which in turn held two boxes of each clone with a starting number of two shoots each. Plants were given sufficient time to establish until overall net new growth in form of new shoot production was observed. After this initial establishment, a one week warming phase for heat treatments preceded the four-week stress period throughout August 2023, followed by cool-down phase and subsequently a total of six weeks recovery. During the stress period heat stress was a permanent stressor, while hypoosmotic stress was induced in pulsed salinity drops to simulated inflow events. For this, filtered (Aqua Medic Antiphos FE) water (50/50 VE and tap water) was added to the aquaria over two to three hours until the desired salinity of 27 was reached. The same water was used to refill evaporated water in the other treatments to keep salinity levels at 32.5. Photosynthetic performance assessments of T. testudinum were conducted at the end of the stress period, after three and finally six weeks of recovery using a Pulse-Amplitude-Modulation (PAM) chlorophyll fluorometer (PAM2500, Heinz Walz GmbH, Germany). Measurements were taken from approximately three hours before to three hours after midday. The second or third oldest leaf was chosen for measurements and a dark leaf clip equipped with a sliding shutter was attached to the midsection of the leaf. Then the shutter was closed for a minimum of 10 minutes to allow for dark adaptation, as this was crucial to later determine the maximum quantum yield Fv/Fm. Subsequently the leaf was exposed to a consecutive series of 11 actinic light intensities (PAR 0–1579 µmol m^-2 s^-1) at 20 second intervals. For each treatment four randomly selected shoots per clone were measured, resulting in a total of 16 samples per treatment.
Keywords: Growth/Morphology; heat stress; Laboratory experiment; Osmotic stress; Photosynthetic parameters; tropical seagrass